Analisis Analisis Pengelolaan Keuangan Bumdesma Dalam Rangka Memberdayakan Potensi Desa Di Kabupaten Banyumas: Pengelolaan Keuangan BUMDesma. - Yubiharto Yubiharto; Siti Maesaroh; Tjahjani Murdijaningsih (Jurnal Proaksi, 2024)
Good financial management is the key to the success of a business, so this study will explore problems related to financial management, related to accounting information by parties who need it for decision making of the Joint BUMDesma. Good BUMDesma financial management can empower regional potential. This study aims to determine how far BUMDesma financial management is in order to empower village potential. This study was conducted in Banyumas Regency with BUMDesma research objects in all Sub-districts in Banyumas Regency. The research method is a qualitative method and the data collection techniques used are in-depth interviews, focus group discussions, and documentation using triangulation. The sample in this study was 10 BUMDesma consisting of managers and financial holders who are directly in contact with BUMDesma financial reports and village assistants so that the total sample is 30 informants. Based on the results of in-depth interviews, the results of the study are that good financial management is needed, especially in standardized financial reporting using an information system and the existence of opportunities for business development. Good financial management must be supported by an accounting information system in the form of BUMDesma financial applications, adequate human resources and supporting local government policies.